Knowledge deficits and barriers to performing soft-tissue coverage procedures: An analysis of participants in an orthopaedic surgical skills training course in Mexico. Issue 4 (December 2019) - Albright, Patrick D.; Mackechnie, Madeline C.; Jackson, J. Hunter; Chopra, Aman; Holler, Jordan T.; Flores Biard, Antonio; Padilla Rojas, Luis G.; Morshed, Saam; Miclau, Theodore; Shearer, David W.; Terry, Michael J.
Abstract: Background: An increasing number of traumatic injuries in low- and low-middle-income countries (LICs/LMICs) have coexisting injuries requiring soft-tissue coverage (flaps). Yet, there is a lack of subspecialty care and flap training in Latin America. This study assesses the effectiveness of a surgical skills training course in improving rotational and free flap knowledge and identifies barriers to performing these types of flaps. Methods: Participants attending a surgical skills training course in Guadalajara, Mexico completed a pre/postcourse flaps knowledge survey consisting of 15 questions from the plastic surgery in-training examination and also completed a 7-point Likert survey regarding perceived barriers to performing flaps at their institution. Results: Of the course participants, 17 (44.7%) completed the precourse knowledge survey, 24 (63.2%) completed the postcourse survey, and 37 (97.4%) completed the barriers survey. Scores improved from pre- to postcourse knowledge surveys (39.6% to 53.6%, P = .005). Plastic surgery subsection scores also improved (39.0% to 60.4%, P = .003). Twenty-five percent of attendees received prior flap training and had plastic surgeons available to perform flaps. Few participants (38.9%) reported flap procedures being commonly completed at their hospitals. Participants stating that flaps were uncommon in their hospital reported more institutional barriers and less access to dermatomes. These participants also reported lack of operating room and surgical personnel availability. Conclusion: A surgical skills training course may be useful in improving knowledge of soft-tissue coverage procedures. There are also modifiable physician and institutional barriers that can improve the ability to perform rotational and free flaps as identified by the course participants.